Symbolic Interactionism in Contemporary Digital Society - Muhammad Faiq, Habadza Rahman; Rofiq, Mohammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
the rapid development of digital technology has transformed patterns of social interaction and the construction of social meaning. Interactions that were previously dominated by face-to-face encounters are now increasingly mediated through digital platforms, visual symbols, and algorithmic systems. This article aims to reinterpret George Herbert Mead’s theory of symbolic interactionism in the context of contemporary digital society. This study employs a qualitative approach using a systematic literature review of classical symbolic interactionism texts and recent scholarly works on digital media and online identity. The findings indicate that Mead’s core concepts of mind, self, and society remain analytically relevant for understanding social interaction in digital environments. However, these concepts require conceptual expansion to account for the role of digital symbols, platform architectures, and algorithmic mediation. This study argues that symbolic interactionism retains its theoretical significance in the digital era by adapting to technologically mediated social realities.